Online Personal Tutoring System - Kanagesswary, Shanmuganathan (2013)
Nowadays, most of the primary schools in Malaysia are still using courseware such as CD during teaching as a learning material. Students also depend on web based learning programme to study the subject that required them to pay. However, not everybody able to pay for the online educational programme such as Score A programme. Besides that, teachers are not participating in the web based learning application as they not play role to update notes and assessment every time. With the growing of technologies, the situation should be changed. The Online Personal Tutoring System (OPTS) can provide the solution for the above situation. The objective of OPTS is to provide medium for teacher to share learning and teaching material towards providing platform for the for year 4 science students to the current KSSR (KURIKULUM STANDARD SEKOLAH RENDAH) which is based on band system. The OPTS is mainly for science subject at primary school which contain one topic. There are three targeted users in this system which is a single administrator, teacher and student. They are carried out different kind of roles as stated in user requirement. Waterfall model has been chosen as the method to develop this system which is planning, requirement analysis, implementation and testing. This methodology is chosen because it attempts to reduce inherent project risk by breaking a project into smaller segments, provides easy to change during the development process and it is suitable used on developing OPTS. The OPTS is expected to become an educational tutoring aid for pupils and teachers. Moreover, only teacher can participate in OPTS as the teaching material provider.